2013
DOI: 10.1016/j.ccr.2012.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of miRNA-708 by Polycomb Group Promotes Metastases by Calcium-Induced Cell Migration

Abstract: The progression of cancer to metastatic disease is a major cause of death. We identified miR-708 being transcriptionally repressed by polycomb repressor complex 2-induced H3K27 trimethylation in metastatic breast cancer. miR-708 targets the endoplasmic reticulum protein neuronatin to decrease intracellular calcium level, resulting in reduction of activation of ERK and FAK, decreased cell migration, and impaired metastases. Ectopic expression of neuronatin refractory to suppression by miR-708 rescued cell migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(155 citation statements)
references
References 64 publications
7
147
0
1
Order By: Relevance
“…According to our unpublished data of NGS results between MDA-MB-231 and MCF7, miR-218 is higher in MDA-MB-231 while miR-708 is lower in MDA-MB-231 comparing to MCF7. In addition, miR-708 expression was validated in our previous study [25]. In consistence with NGS data and previous study, miR-218 had higher expression levels in the metastatic breast cancer cells (MDA-MB-231) than in the non-metastatic cells (MCF7).…”
Section: Resultssupporting
confidence: 66%
“…According to our unpublished data of NGS results between MDA-MB-231 and MCF7, miR-218 is higher in MDA-MB-231 while miR-708 is lower in MDA-MB-231 comparing to MCF7. In addition, miR-708 expression was validated in our previous study [25]. In consistence with NGS data and previous study, miR-218 had higher expression levels in the metastatic breast cancer cells (MDA-MB-231) than in the non-metastatic cells (MCF7).…”
Section: Resultssupporting
confidence: 66%
“…However, this study did not report the expression level of the TMEM88 protein, and it is therefore unclear whether the enhanced invasion of NSCLC cells was due to suppression of TMEM88 transcription or some other mechanism. Moreover, conflicting reports have suggested that miR708 suppresses migration and invasion of tumor cells (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that some genes previously linked to GABAergic interneuron differentiation, such as Sox11, were expressed by cells in both cluster 2 and 3 ( Figure 4M-P). Cells in the lateral margin of the MGE expressed genes belonging to cluster 4/5, including the cytoskeleton regulator Gap43 [34] and the transmembrane protein gene neuronatin (Nnat) ( Figure 4U-X), both of which have previously been linked to cell migration [34,35]. The expression of several genes unique to cluster 4/ 5 is maintained in migrating interneurons as they propagate towards the cortex.…”
Section: Spatial Pattern Validation Of Medial Ganglionic Eminence Tramentioning
confidence: 99%